2004
DOI: 10.4049/jimmunol.173.8.5138
|View full text |Cite
|
Sign up to set email alerts
|

Preapoptotic Phenotype of Viral Epitope-Specific CD8 T Cells Precludes Memory Development and Is an Intrinsic Property of the Epitope

Abstract: Virus-specific CD8 T cells after clearance of infection reduce their number in lymphoid organs by apoptotic death and by migration into peripheral tissues. During and after infection, many lymphocytic choriomeningitis virus (LCMV)-specific CD8 T cells in lymphoid but not peripheral tissues are in a preapoptotic state, as detected by the early apoptosis marker annexin V. In this report, we investigated the significance of this preapoptotic state and how it may be influenced by viral epitope specificity. Stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…2A and data not shown). This is consistent with a previous study of LCMV infection showing similarly high levels of annexin V staining in virusspecific CD8 ϩ T cells (48). In comparing the T cells in WT and CD40…”
Section: Reduced Memory Cd8 ϩ T Cells Numbers In Cd40 ϫ/ϫ Hosts Is Nosupporting
confidence: 80%
“…2A and data not shown). This is consistent with a previous study of LCMV infection showing similarly high levels of annexin V staining in virusspecific CD8 ϩ T cells (48). In comparing the T cells in WT and CD40…”
Section: Reduced Memory Cd8 ϩ T Cells Numbers In Cd40 ϫ/ϫ Hosts Is Nosupporting
confidence: 80%
“…Becker et al (21) have reported that the CD8 ϩ T cell responses to most of epitopes, including NP396, were only slightly, if any, affected after primary infection, whereas CD8 ϩ T cell response to one epitope (GP33) did show a rather dramatic requirement for IL-15. Wang et al (35) showed that CD8 ϩ T cells specific to LCMV epitopes NP396 and GP33 differed in their preapoptotic state, with NP396-specific T cells binding more annexin V than GP33-specifc T cells during the expansion phase on day 8 after LCMV infection. These results suggest that population of T cells specific to different epitopes can have different properties such as IL-15 dependency during the expansion phase after acute infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the LCMV murine model, many virus-specific CD8 T cells in lymphoid organs are in a preapoptotic state (Annexin-V þ ), which was shown to preclude the development of functional memory. 136 In HIV infection, downregulation of Bcl-2 and Bcl-x L was detected on peripheral blood 93,95 and lymph node CD8 T cells, 94 priming these cells for autonomous cell death, 93 and contributing to the deletion of HIV-specific memory T cells. 95 Bcl-2 downregulation and CTL apoptosis may also be induced by high doses of virus during the primary viral infection, causing the rapid deletion of high avidity virus-specific CTLs, as suggested in a murine model.…”
Section: Impairment Of Hiv-specific Cd8 T Cellsmentioning
confidence: 99%